Powstanie i działalność Rosyjsko-Litewskiej Komisji Historyków (2006−2018): The Establishment and Activity of Russian-Lithuanian Commission of Historians (2006–2018) - Letlo, Paweł (Przegląd Wschodnioeuropejski, 2019)
The issues of the assessment of the common past play an important role in the mutual relations of the Russian Federation and the Baltic States. In Russian opinion, the establishment of joint commissions of historians was to reduce tensions on this line and improve the image of Russia abroad. Lithuania was the first of the Baltic countries to express a desire to dialogue with Russia on the common past – in 2006, the Joint Russian-Lithuanian was established. According to the declaration, the main goal of both committees was to activate scientific research, the conclusions of which could also be used in inter-state relations. The work of both committees was focused on historical events of the 20th century, and the main problem was the dispute over the interpretation of the seizure of the Baltic states by the USSR. In 2014, in connection with the events in Ukraine, Lithuania suspended the activities of the commission.